Incidence and Risk Factors of Lower Extremity Lymphedema After Gynecologic Surgery in Ovarian Cancer. Issue 7 (September 2016) - Ki, Eun Young; Park, Jong Sup; Lee, Keun Ho; Hur, Soo Young
Abstract : Objective: There is no standard method to establish an early diagnosis of lower extremity lymphedema (LEL). Lower extremity lymphedema can be diagnosed by physical examination and laboratory tests when patients complain of typical clinical symptoms. The objective of this study was to investigate the incidence and risk factors of LEL in patients with ovarian cancer. Methods: The medical records were reviewed retrospectively in patients with ovarian cancer treated at Seoul St. Mary's Hospital from January 2000 to July 2014. Results: A total of 413 patients with epithelial ovarian cancer were analyzed. Forty-six patients (11.1%) developed LEL, and 67.4% of these patients had LEL within 1 year after surgery. The mean number of resected lymph nodes (LNs) was larger in patients with LEL (43.1 ± 16.7; range, 12–80) than in those without (32.3 ± 19.8; range, 0–99) ( P < 0.0001). The number of resected LNs was significantly associated with the occurrence of LEL (odds ratio, 1.025; 95% confidence interval, 1.005–1.045; P < 0.05). Conclusion: A significant proportion of patients with ovarian cancer could develop LEL after surgery. This study suggests that the occurrence of LEL is associated with the number of resected LNs.